- Business Model Planning for the Situmurun Waterfall Tourism Attraction Based on the Business Model Canvas - Arie Afandi Manalu (Wonderful-Journal of Tourism Destination, 2026)
Situmurun Waterfall, located in Jonggi Nihuta Village, Toba Regency, is one of the geosites within the UNESCO Global Geopark of Lake Toba, holding great potential as a natural tourist attraction. However, the management of this destination still faces several challenges, including damaged infrastructure, weak local institutions, and the absence of a structured business strategy. This study aims to analyze the internal and external conditions of Situmurun Waterfall management through SWOT analysis and to formulate a business model plan using the Business Model Canvas (BMC). The research employed a qualitative approach with data collection techniques including observation, in-depth interviews, and document review. The findings indicate that development strategies should focus on leveraging the natural uniqueness of the waterfall through digital promotion, enhancing local human resource capacity, improving supporting facilities, and strengthening multi-stakeholder collaboration. The integration of SWOT analysis into the nine elements of BMC resulted in an adaptive, applicable, and sustainable business model. Theoretically, this study contributes to the literature on applying BMC to natural tourist attractions, an area that remains underexplored. Practically, the results provide guidance for local governments, communities, and private partners in developing Situmurun Waterfall into an inclusive, competitive, and globally recognized destination.